A computational approach for solving elasto-statics problems. (2021) - Kumar, Manish; Rajiyan, Jogesh; Gupta, Pankaj
Abstract: Meshless methods are the new computational techniques to solve elasto-statics problem. This technique has an advantage as it does not require any surface discretization unlike finite element method (FEM). These techniques also provide best results and save computational timing. The elasto-statics problem pertaining to external loading often defined using high order differential equation, which become a challenging task for analytical modelling and simulation. Thus, in present work new computational meshless methods viz. Element Free Galerkin Method (EFGM) and Meshless Local Petro-Galerkin (MLPG) have been used to solve elasto-statics problems for obtaining the higher approximation value compare to FEM. This technique takes the information of local nodes in order to develop the equilibrium equation, as a consequence it converge faster and accurate.